Two new miniature species of the fish genus Priocharax from the Rio Tapajós and Amazonas drainages, Pará, Brazil (Teleostei: Characiformes: Characidae) - Mattox, George M.T.; Lima, Flávio C.T.; Britz, Ralf; Souza, Camila S. [UNESP]; Oliveira, Claudio [UNESP] (Pensoft Publishers, 2024)
The miniature fish genus Priocharax currently comprises seven valid species: P. ariel, P. britzi, P. marupiara, P. nanus, P. pygmaeus, P. toledopizae and P. varii. Except for P. ariel and P. pygmaeus, all the species are endemic to Brazil. Priocharax is characterized by several paedomorphic features such as reductions in the laterosensory system, number of fin rays, and ossification of parts of the skull. The most striking reductive character of Priocharax is the larval rayless pectoral fin in which most of its ossified endoskeletal elements are absent. We describe herein two new species of Priocharax from the vicinity of Santarém municipality, Pará state, Brazil. Both new species are distinguished from each other and from congeners by a combination of morphological features (i.e., osteological, morphometric, and meristic data) and molecular information (i.e., DNA barcode). We also present an updated maximum likelihood tree which now includes all nine species of Priocharax.
Keywords: Anatomy; DNA barcode; integrative taxonomy; miniature tetra; Neotropics; systematics